Rules of Thumb in Data Engineering - Gray, Jim; Shenay, Preshant (ICDE '00 Proceedings of the 16th International Conference on Data Engineering, 1999)
This paper reexamines the rules of thumb for the design of data storage systems. Briefly, it looks at storage, processing, and networking costs, ratios, and trends with a particular focus on performance and price/performance. Amdahl's ratio laws for system design need only slight revision after 35 years-the major change being the increased use of RAM. An analysis also indicates storage should be used to cache both database and Web data to save disk bandwidth, network bandwidth, and people's time. Surprisingly, the 5-minute rule for disk caching becomes a cache-everything rule for Web caching.